2019
DOI: 10.3126/ajms.v10i4.23990
|View full text |Cite
|
Sign up to set email alerts
|

Post-Traumatic Stress Disorder among Emergency Medical Services Personnel: A Cross-sectional Study

Abstract: Background: Post-Traumatic Stress Disorder is characterized by directly experiencing traumatic events or witnessing, learning, or repetitively experiencing the details of these events. High risk occupations (i.e., EMS personnel) frequently encounter traumatic eventscoping with events exceeding the range of human experiences. Regional lack of studies necessitated the need to report the prevalence of PTSD among healthcare providers in Saudi Arabia (SA). Aims and Objective: To explore the prevalence of PTSD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 13 publications
0
17
1
Order By: Relevance
“…The estimate of the prevalence of distress from the present study indicated that more than half of the general public in Saudi Arabia were under severe distress during the pandemic period. The estimated prevalence among the general public was greater than what observed among workers attending emergency medical and fire services in the country (Qumri and Osman, 2014; Alghamdi et al, 2017; Alaqeel et al, 2019). A study from China also reported such a high prevalence among the general public during the current pandemic (Wang et al, 2020).…”
Section: Discussionmentioning
confidence: 65%
“…The estimate of the prevalence of distress from the present study indicated that more than half of the general public in Saudi Arabia were under severe distress during the pandemic period. The estimated prevalence among the general public was greater than what observed among workers attending emergency medical and fire services in the country (Qumri and Osman, 2014; Alghamdi et al, 2017; Alaqeel et al, 2019). A study from China also reported such a high prevalence among the general public during the current pandemic (Wang et al, 2020).…”
Section: Discussionmentioning
confidence: 65%
“…PTSD can occur in people who have experienced or witnessed traumatic events such as natural disasters, severe accidents, terrorist acts, wars, and sexual violence ( Piotrowski & Range, 2019 ). PTSD began to be recognized as a mental disorder in the 1980s and is characterized by continuous symptoms associated with traumatic events such as intrusive dreams or memories, changes in mood, avoidance, reactivity, and arousal ( Alaqeel et al, 2019 ). PTSD symptoms can occur in a week to 30 years after the traumatic experience; 30% of cases recover on their own without treatment, but 40% of patients continue to experience symptoms (i.e., panic attacks, hallucinations, aggressive tendencies, impulse control disorders, depression, drug abuse, decreased concentration, and problems with cognitive functions) ( Panagioti et al, 2015 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…PTSD can be classified into four symptoms: intrusive thoughts, avoiding reminders, negative thoughts and feelings, and arousal and reactive symptoms; the severity of these symptoms may vary ( Alaqeel et al, 2019 ; Lai et al, 2018 ; Panagioti et al, 2015 ; Piotrowski & Range, 2019 ). Intrusive thoughts refer to the intrusion of painful memories or emotions to the consciousness, resulting in feeling or acting as if the patient is experiencing the actual trauma, and are marked by physiological responses such as severe mental pain and sudden increases in heartbeat ( Piotrowski & Range, 2019 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In Saudi Arabia, estimates of PTSD prevalence in ambulance workers have varied, but rates are higher than those reported in European countries. One study in Riyadh city estimated PTSD among paramedics from King Khalid Abdul Aziz Medical City (KAMC) and found that 30% of paramedics were experiencing PTSD [ 13 ]. Another study among Saudi Red Crescent Authority ambulance personnel who worked in Makkah city found 41% of paramedics were affected by PTSD [ 14 ].…”
Section: Introductionmentioning
confidence: 99%